Explaining The Territoriality Of Fundamentalist Organizations in Fragile States(Case Study: ISIS in Libya) - Morad Kaviani Rad; Hadi Aazami; Majid Rasouli; Ahmad Bakhshi (تحقیقات کاربردی علوم جغرافیایی)
Fundamentalism is one of the security issues of today's world, and the Territorialize and , Territoriality of  fundamentalist terrorist groups has attracted a large part of the world's security literature.  Over the past decade, Southwest Asia and North Africa have emerged from domestic crises and transnational power interference, the focus of the emergence and expansion of radical ideas that impose huge costs on the regional and trans-regional countries of the world. Meanwhile, the northern continent of Africa, and in particular the country of Libya, as a fragile state emerging from the internalities and role of the regional interventionist powers, has provided opportunities for the expansion of ISIS's fundamentalist organization.The present study is based on the descriptive-analytical nature of the hypothesis that based on internal factors such as strategic position and huge oil resources, the crisis of legitimacy, spatial inequalities (axis-margin), the weakness of national correlators, weakness of central government power, Interventions of regional and global powers territoriality have been provided a platform for fundamentalist organizations such as ISIL in Libya, and the data and information required for research has been compiled in a library-based way . The results of the study showed that the fragility of the government in North Africa, in particular Libya, Territorialize and , Territoriality grounds have provided for ISIL's .